OECD Science, Technology and Industry Scoreboard 2017 : the digital transformation (Paris, 2017)
"The biennial OECD Science, Technology and Industry (STI) Scoreboard features indicators traditionally used to monitor developments in science, technology, innovation and industry, and complements them with experimental indicators that provide new insights into areas of policy interest. These include: investment in knowledge-based capital, skills in the digital era, the international mobility of researchers, the digital transformation in firms and industries, innovation strategies, the internationalisation of research, changing patterns in trade competitiveness and productivity, as well as the use of technology in everyday life."